PATHET SEBAGAI STRUKTUR ADEGAN WAYANG KULIT JAWATIMURAN SUBGAYA MALANGAN - Pangestu, Dwi Cahyo; Suhita, Raheni; Suryanto, Edy (Panggung, 2023)
Malangan’s puppet is a shadow puppet that grows and develops in East Jawa, precisely in the Greater Malangarea. Malangan’s puppet differs from other styles in the scene structure department, which is covered by fivepathet (Javanese gamelan modes) concepts. The purpose of this research is to describe the structure of thescene using five pathet concepts with the sample of the Malangan’s puppet script, Gathotkaca Lair. ThisStudy applied the descriptive qualitative method. The research data were drawn from the data source of theMalangan’s puppet script with the Gathotkaca Lair’s play. The data collection employed content analysistechniques by evaluating several character dialogues that represent the scene structure in each pathet. Thedata analysis technique implemented the Miles & Huberman interactive model. The results of the studysuggest that the scene structure in the Gathotkaca Lair’s script is well packaged into five pathets. The fivepathets are pathet sepuluh (tenth), pathet wolu (eight), pathet sanga (ninth), pathet miring, and pathetserang. Pathet sepuluh serves as the opening act, while pathet serang is the closing act.Keywords: Structur of the Scene,, Malangan’s Puppet, Pathet